2022
DOI: 10.7717/peerj.13938
|View full text |Cite
|
Sign up to set email alerts
|

Association between changes in social capital and mental well-being among older people in China

Abstract: Background The mental well-being of older people has become social concern under aging times in China. Social capital has been linked to mental well-being. Our aims were to explore how social capital and the state of mental well-being of older people were changing and what the relationship between them was. Methods Data were from six waves of the China Family Panel Studies that were conducted between 2010 and 2020, and a total of 1,055 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
1
0
Order By: Relevance
“…This approach permits an in-depth exploration of the associations between variables over time. Despite the growing acknowledgment of the impact of psychosocial factors on psychological health of older adults, as evidenced by existing research, 10 , 17 , 23 , 27 , 29 much of the current literature focused narrowly on single factors such as loneliness or social capital, 17 , 27 often relying on cross-sectional study designs. This study addressed the gap in the field by thoroughly examining four key psychosocial factors in the older population—loneliness, social isolation, perceived social support, and social capital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach permits an in-depth exploration of the associations between variables over time. Despite the growing acknowledgment of the impact of psychosocial factors on psychological health of older adults, as evidenced by existing research, 10 , 17 , 23 , 27 , 29 much of the current literature focused narrowly on single factors such as loneliness or social capital, 17 , 27 often relying on cross-sectional study designs. This study addressed the gap in the field by thoroughly examining four key psychosocial factors in the older population—loneliness, social isolation, perceived social support, and social capital.…”
Section: Discussionmentioning
confidence: 99%
“…26 Cohort studies have identified that higher levels of cognitive social capital act as protective factors against common mental disorders. 27 , 28 Koryu’s longitudinal study highlighted a negative association between depressive symptoms and dimensions of social capital, namely social cohesion, reciprocity, and community-level reciprocity. 29 …”
Section: Introductionmentioning
confidence: 99%
“…The instruments have high reliability in the CFPS of adults, which encompass areas such as mental health, social capital and parental engagement. The Cronbach’s alpha ranges from 0.61 to 0.85 [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…While cognitive social capital, refers to trust, values, beliefs, reciprocity. and other psychological processes [26, 27]. Some studies have proven that a close relationship exists between structural, cognitive social capital, and life satisfaction among older people [28, 29].…”
Section: Introductionmentioning
confidence: 99%